Fisioterapia respiratoria en pacientes con fibrosis pulmonar idiopática en adultos mayores, en el Centro Fisioterres Ventanas-Los Ríos, octubre 2018 – abril 2019 - Peñaloza Morales, Janio Carlos (2019)
The researcher project focuses on a habitual restrictive respiratory pathology, the Idiopathic Pulmonary Fibrosis mostly affects older adults or from 50 years and above. To establish the benefit of respiratory physiotherapy in patients with Idiopathic Pulmonary Fibrosis in older adults, in the center "FISIOTERRES” Ventanas-Los Ríos. In the research project a study was made using the deductive method, with a quantitative approach, with the type of research used, experimental, documentary, exploratory and longitudinal. The population of our research work corresponds to the human resource that we have used as a reference, in this case are the 35 elderly patients with Idiopathic Pulmonary Fibrosis who went to the rehabilitation center privately general integral "FISIOTERRES" Code PF No: ACESS-2018-Z05-0054693 of the canton Ventanas of the territory of Los Ríos during the second semester of 2018 and the study sample due to the size of the population that is relatively small, we have taken the consideration of working with the 35 elderly patients diagnosed with Idiopathic Pulmonary Fibrosis. We use the technique of unscientific and direct scientific observation, a direct structured interview with the Respiratory Therapist and the collection of statistical data based on the values of the tests performed in the sample. 100% of the sample joined the treatment by diagnosis of Idiopathic Pulmonary Fibrosis. It was obtained as a result that the techniques of Respiratory Physiotherapy were effective in a 91% giving as a result of 9% of ineffectiveness and 3 patients of the sample deserted the treatment. It was important to demonstrate directly the importance of performing the techniques through a protocol for the type of patient depending on the needs of each one and whether they will have a positive improvement in their pulmonary capacities and in their adaptation to the effort.